THE RELATION BETWEEN NURSE THERAPEUTIC COMMUNICATION WITH PATIENT SATISFACTION AT JATIROTO PUSKESMAS, LUMAJANG - Umi Kulsum, Siti; Purnama, Yugi Hari Chandra; Atik Maryati, Syska (International Islamic Medicine Forum, 2022)
Therapeutic Communication is defined as nurses communication techniques to provide support and information to patients aims to therapy. When the nurses provide good communication, it will bind a good relation between nurses and patient so that the patient will be satisfied with the services. This research aims to determine the relation between nurse therapeutic communication with inpatient satisfaction at Jatiroto publich health centre, Lumajang. This research was using correlational design with cross sectional approach. The sampling method was using incidental sampling and sampling technique was using nonprobability sampling. The data collection was conducted by observational and questionnaires. The result of this research shows that 73,3% nurse therapeutic communication are in good category and 26,7% nurse therapeutic communication are in passably category. The satisfaction level of patient 53,3% are satisfied, 13,3% are unsatisfied and 53,3% are very unsatisfied. The statistic analytical by Spearmean Rank was obtained p value 0.046 <0.05, it means there is a relation between nurse therapeutic communication with inpatient satisfaction at Jatirotopublich health centre, Lumajang.It means that the better nurse's therapeutic communication is, the more satisfied the patient is. Nurse's therapeutic communication is in good category and patient satisfaction is in satisfied category. The practice of health services through therapeutic communication by nurses at the Puskesmas is an example and a small part of the lessons and application of Akhlaq in a profession.